Double-blind randomised controlled trial of vitamin D3 supplementation for the prevention of acute respiratory infection in older adults and their carers (ViDiFlu). Issue 10 (10th June 2015) - Martineau, Adrian R; Hanifa, Yasmeen; Witt, Karolina D; Barnes, Neil C; Hooper, Richard L; Patel, Mital; Stevens, Natasha; Enayat, Zinat; Balayah, Zuhur; Syed, Asmat; Knight, Aishah; Jolliffe, David A; et al.
Abstract : Rationale: Low-dose vitamin D supplementation is already recommended in older adults for prevention of fractures and falls, but clinical trials investigating whether higher doses could provide additional protection against acute respiratory infection (ARI) are lacking. Objective: To conduct a clinical trial of high-dose versus low-dose vitamin D3 supplementation for ARI prevention in residents of sheltered-accommodation housing blocks ('schemes') and their carers in London, UK. Measurements and methods: Fifty-four schemes (137 individual participants) were allocated to the active intervention (vitamin D3 2.4 mg once every 2 months +10 μg daily for residents, 3 mg once every 2 months for carers), and 54 schemes with 103 participants were allocated to control (placebo once every 2 months +vitamin D3 10 μg daily for residents, placebo once every 2 months for carers) for 1 year. Primary outcome was time to first ARI; secondary outcomes included time to first upper/lower respiratory infection (URI/LRI, analysed separately), and symptom duration. Main results: Inadequate vitamin D status was common at baseline: 220/240 (92%) participants had serum 25(OH)D concentration <75 nmol/L. The active intervention did not influence time to first ARI (adjusted HR (aHR) 1.18, 95% CI 0.80 to 1.74, p=0.42). When URI and LRI were analysed separately, allocation to the active intervention was associated with increased risk of URI (aHR 1.48, 95% CI 1.02 to 2.16, p=0.039) and increased duration of URI symptoms (median 7.0 vs 5.0 days for active vs control, adjusted ratio of geometric means 1.34, 95% CI 1.09 to 1.65, p=0.005), but not with altered risk or duration of LRI. Conclusions: Addition of intermittent bolus-dose vitamin D3 supplementation to a daily low-dose regimen did not influence risk of ARI in older adults and their carers, but was associated with increased risk and duration of URI. Trial registration number: clinicaltrials.gov NCT01069874 .